LITERASI PEMASARAN DIGITAL USAHA BATU BATA MERAH DI NEGERI HATU KECAMATAN LEIHITU BARAT KABUPATEN MALUKU TENGAH - Sarlotha Yulliana Purimahua; Yonette Maya Tupamahu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2024)
The red brick business in Hatu Village has been carried out by the community for a long time, but the marketing method is still conventional, does not include other parties such as building materials shops, and has not carried out promotions via social media. Community service is carried out with the aim of increasing partners' knowledge about digital marketing of red bricks. The solution offered consists of a preparation stage, implementation stage and evaluation stage. The results of the activity in frequency analysis showed that the lowest pre-test score was 10 for 2 people and the highest score was 40 for 13 people, with an average score of 37. Meanwhile, the lowest post-test score was 60 for 18 people and the highest score was 80 for 4 people. people with an average score of 69. This means that the average post-test score is greater than the average pre-test score, this indicates that digital marketing literacy activities are running effectively and increasing the knowledge of red brick entrepreneurs.